2022
DOI: 10.1111/1756-185x.14272
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor necrosis factor‐α inhibitors and liver cirrhosis in patients with rheumatoid arthritis: A nationwide population‐based nested case‐control study

Abstract: Aim: Results from various studies are controversial regarding long-term hepatic effects of tumor necrosis factor (TNF)α inhibitors. Here we aimed to investigate the development of liver cirrhosis with TNFα inhibitors use in patients with rheumatoid arthritis (RA). Method: This nested case-control study was based on the National Health Insurance Research Database (January 1, 2000 to December 31, 2008) of Taiwan. We identified 559 adult RA patients who developed liver cirrhosis, and 1055 matched control RA patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“… 15 In terms of liver damage, ie, cirrhosis, a multicenter study revealed no correlation with the development of cirrhosis in RA patients. 16 In terms of hepatitis virus infection, Brunasso et al published a systematic review 17 which included 153 patients with HCV treated with anti-TNF-α drugs between 1999 and 2010, including 91 with RA, 7 with psoriatic arthritis, 8 with psoriasis, 8 with both psoriasis and psoriatic arthritis, 6 with CD, and 14 with other chronic inflammatory diseases. A total of 110 cases were treated with ETN, with only one clearly diagnosed case of worsening HCV hepatitis and five suspected cases.…”
Section: Tnf-α Inhibitormentioning
confidence: 99%
“… 15 In terms of liver damage, ie, cirrhosis, a multicenter study revealed no correlation with the development of cirrhosis in RA patients. 16 In terms of hepatitis virus infection, Brunasso et al published a systematic review 17 which included 153 patients with HCV treated with anti-TNF-α drugs between 1999 and 2010, including 91 with RA, 7 with psoriatic arthritis, 8 with psoriasis, 8 with both psoriasis and psoriatic arthritis, 6 with CD, and 14 with other chronic inflammatory diseases. A total of 110 cases were treated with ETN, with only one clearly diagnosed case of worsening HCV hepatitis and five suspected cases.…”
Section: Tnf-α Inhibitormentioning
confidence: 99%
“…The TNF signaling pathway was also identified as a significant pathway, Tumor necrosis factor (TNF) is multi-functional cytokine which has an important role in pro-inflammatory cytokine. A study showed that TNF is secreted by inflammatory cells which are involved in inflammation-associated carcinogenesis [60]. Our own analysis showed that the major identified putative targets were also involved in the NF-kappa B signaling pathway which plays a key role in inflammatory and immune responses as well as regulation genes involved in cell death differentiation and proliferation [61].…”
Section: Gene Ontology and Pathway Enrichment Analysismentioning
confidence: 97%
“…The IL-17 signaling pathway promotes neutrophil mobility via T cell activation, which help against inflammatory illnesses such as rheumatoid arthritis (Raucci et al 2022). TNF signaling is a multifunctional cytokine and plays an important role in pro-inflammatory cytokine (Chen et al 2022). NF-kappa B signaling pathway play important role in inflammatory and immunological responses, as well as regulating genes involved in cell death, differentiation, and proliferation (Cao et al 2022).…”
Section: Gene Ontology and Pathway Enrichment Analysismentioning
confidence: 99%
“…We evaluate the drug-likeliness of the candidate drug compounds using Molinspiration an online software (Molinspiration 2011) for prediction of molecular properties. We applied Lipinski rule of five which state that "drug-like" molecules have logP≤ 5 , molecular weight ≤ 500 , hydrogen bond acceptors ≤ 10 and hydrogen bond donors ≤ 5 (Zhang and Wilkinson 2007;Chen et al 2020). The results in Table 2 indicate that the all four candidate drug compounds were within the limits of Lipinski's rule.…”
Section: Molecular Docking Evaluationmentioning
confidence: 99%
See 1 more Smart Citation